Peran Penyuluh Agama dalam Membina Majelis Taklim - Nini Arniyani; Suryati Suryati; Neni Noviza (Journal of Society Counseling, 2023)
This thesis research is entitled "The Role of Religious Extension Workers in Fostering the Taklim Assembly in Sukajadi Village, Sungai Rotan District, Muara Enim Regency". To find out the role of religious instructors in fostering taklim assemblies, to find out the supporting and inhibiting factors of the role of religious instructors in fostering taklim assemblies. This type of research is field research. To get the desired research results, the research method the writer uses is descriptive analysis method, namely direct research on the object of research to obtain the necessary data. The data collection technique that the authors use in this research is to use observation, interview and documentation techniques. Sources of data in this writing were obtained from 4 respondents, namely 1 Religious Extension Officer, 3 women Taklim Council. The data analysis technique used is descriptive analysis method by collecting data on the factors that support the research. The results of the study show that religious extension workers are capable as educators (muaddib), as information straighteners (musaddin). As a reformer (Mujaddid), As a unifier (muwahid), a supporting factor in fostering the Taklim Assembly, namely Religious Counselors who are able to be responsible for being the delivery of da'wah to the community to provide direction and understanding of religion correctly according to the Shari'a, the inhibiting factor in fostering the Taklim Assembly is the lack of public interest in participating in the activities of the Taklim Assembly and also a lack of understanding of the Koran and reading it.